EKSPLORASI KEANEKARAGAMAN HERPETOFAUNNA DI KECAMATAN GIRIMULYO KABUPATEN KULON PROGO YOGYAKARTA - Tony Febri Qurniawan (Universitas Gadjah Mada, 2012)
The research was aimed to reveal and document hereptofauna from Girimulyo District Kulon Progo Regency,Daerah Istimewa Yogyakarta Province. This research was done from November-Desember 2008 and January-April 2009 in four research locations were Girimulyo, Jatimulyo, Giripurwo and Purwosari. The VES (VisualEncounter Survey) method were used and combined with interview method.. A total of 40 species of herpetofaunaare indentified and includes in to 13 family. Among 40 species, only one (Michrohyla achatina) is endemic to Java.The commonest herpetofaunas along all site were Eutropis multifasciata and Hylarana chalconota.